2006
DOI: 10.1007/s10540-006-9001-4
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Effects of Supplementation with Dehydroepiandrosterone Sulphate or Dexamethasone on Rat Insulin-Secreting Cells Under In Vitro Culture Condition

Abstract: Dehydroepiandrosterone (DHEA) and glucocorticoids are steroid hormones synthesised in the adrenal cortex. Administration of DHEA, its sulphate derivative, DHEAS, and more controversially dexamethasone (DEX), a synthetic glucocorticoid, have beneficial effects in diabetic animals. Cultivating BRIN-BD11 cells for 3 days with either DHEAS (30 muM) or DEX (100 nM), reduced total cell number and reduced cell viability and cellular insulin content. DHEAS-treated cells had poor glucose responsiveness and regulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
(38 reference statements)
1
12
0
1
Order By: Relevance
“…(Ortsäter et al, 2005) Dex 100 nM for 3 d in BRIN-BD 11 cells DEX-treated cells lacked responsiveness to glucose and membrane depolarisation, and both PKA and PKC secretory pathways were desensitised. (Liu et al, 2006) Dex 1 µM concomitant or for 3 h previous culture in rat islets Dex (included in the perifusion solution) has no effect on GSIS. Previous incubation with Dex markedly decrease the 1 st and the 2 nd phases IS under 15 mM glucose.…”
Section: Main Results Referencementioning
confidence: 94%
See 3 more Smart Citations
“…(Ortsäter et al, 2005) Dex 100 nM for 3 d in BRIN-BD 11 cells DEX-treated cells lacked responsiveness to glucose and membrane depolarisation, and both PKA and PKC secretory pathways were desensitised. (Liu et al, 2006) Dex 1 µM concomitant or for 3 h previous culture in rat islets Dex (included in the perifusion solution) has no effect on GSIS. Previous incubation with Dex markedly decrease the 1 st and the 2 nd phases IS under 15 mM glucose.…”
Section: Main Results Referencementioning
confidence: 94%
“…Overall, it appears that GCs act at distal sites by diminishing the efficacy of [Ca 2+ ]i on the secretory response by interfering with the amplifying pathway, although we cannot exclude their possible negative effects also in the mechanisms involved in the rapid first phase insulin secretion (Jeong et al, 2001). The interference of GCs in distal sites of the insulin secretory machinery may explain the wide spectrum of non-glucose insulin secretagogues being inhibited by GCs (Lambillotte et al, 1997;Myrsén-Axcrona et al, 1997;Shao et al, 2004;Liu et al, 2006).…”
Section: Al 2011)mentioning
confidence: 94%
See 2 more Smart Citations
“…12 Liu et al demonstrated that DHEA-S deteriorated glucose control and beta-cell function in vitro. 13 Due to the divergent results concerning the effects of DHEA-S on diabetes and especially insulin resistance, we performed a study to assess the effect of DHEA on insulin resistance and consequently on the glycemic control in patients with impaired glucose tolerance.…”
Section: Introductionmentioning
confidence: 99%